The Invention of Duty: Stoicism as Deontology - Visnjic, Jack, (Philosophia Antiqua ;, 2021)
"Did the ancient Greeks and Romans have a concept of moral duty? Jack Visnjic seeks to settle this long-standing controversy in The Invention of Duty: Stoicism as Deontology. The traditional view of ancient ethics is that it was built on notions of virtue and human flourishing and not on any sense of moral obligation. Visnjic argues that, millennia before Kant, the Stoics already developed a robust notion of moral duty as well as a sophisticated deontological ethics. While most writings of the Stoics perished, their concept of duty lived on and eventually came to influence the modern notion. In fact, it was Kant's encounter with Stoic ideas that seems to have spurred him to formulate a new duty-based morality"--